Discovery of novel per- and polyfluoroalkyl substances (PFASs) at a fire fighting training ground and preliminary investigation of their fate and mobility. (October 2017) - Baduel, Christine; Mueller, Jochen F.; Rotander, Anna; Corfield, John; Gomez-Ramos, Maria-José
Abstract: Aqueous film forming foams (AFFFs) have been released at fire training facilities for several decades resulting in the contamination of soil and groundwater by per- and polyfluoroalkyl substances (PFASs). AFFF compositions are proprietary and may contain a broad range of PFASs for which the chemical structures and degradation products are not known. In this study, high resolution quadrupole-time-of-flight tandem mass spectrometry (LC-QTOF-MS/MS) in combination with data processing using filtering strategies was applied to characterize and elucidate the PFASs present in concrete extracts collected at a fire training ground after the historical use of various AFFF formulations. Twelve different fluorochemical classes, representing more than 60 chemicals, were detected and identified in the concrete extracts. Novel PFASs homologues, unmonitored before in environmental samples such as chlorinated PFSAs, ketone PFSAs, dichlorinated PFSAs and perfluoroalkane sulphonamides( FASAs) were detected in soil samples collected in the vicinity of the fire training ground. Their detection in the soil cores (from 0 to 2 m) give an insight on the potential mobility of these newly identified PFASs. Highlights: PFASs were investigated at a AFFF impacted fire training ground (FTG). AFFF impacted concrete and soil core samples (0–2 m) were analysed by LC-QTOF-MS/MS. Mass defect filtering strategy allowed the detection of untargeted PFASs. Novel PFASs homologues were detected in soil and concrete samples collected at the FTG.